BRICS: From Norm Takers to Norm Makers - Lopes da Cunha, Guilherme; Oliveira, Liziane Paixão Silva; Albergaria de Queiroz, Fábio (Nomos: Revista do Programa de Pós-Graduação em Direito da UFC, 2019)
Abstract Since the end of World War II, the United States and Western Europe have been influencing the definition of rules and norms in the international system, which remain today. After the Cold War, especially in the context of the financial crisis (2008), a challenging debate emerged, analyzing the structure of norms, ideas and institutions and incorporating new interlocutors, such as BRICS countries. Besides, it reinforced investigations about the construction of norms and the articulation of developing countries in this environment. We hypothesize that BRICS seeks to broaden the decision-making process. Methodologically, the postcolonial literature of International Relations (IR), together with theoretical approaches on power studies, offer a welcome opportunity to evaluate the process that motivates BRICS as a driver for altering themselves from rule taker to rule maker. Therefore, it spurs analysis on sectors such as development, finance and international organizations leading us to reflect on to what extent do the new debates corroborate a changing scenario? In so doing, the research intends to evaluate the construction of an international order in which a greater number of States can participate effectively in the formation of norms and values in the interstate system. Keywords: BRICS . Development. Values. Interstate System Resumo Desde o final da Segunda Guerra Mundial, os Estados Unidos e a Europa Ocidental influenciam o estabelecimento de regras e normas no sistema internacional que permanece até hoje. Após a Guerra Fria, especialmente no contexto da crise financeira de 2008, surgiu um debate acerca da estrutura de normas, ideias e instituições e incorporando novos interlocutores, como os países do BRICS. Além disso, o novo cenário internacional reforçou as investigações sobre a construção de normas e a articulação dos países em desenvolvimento nesse ambiente. Metodologicamente, a literatura pós-colonial de Relações Internacionais (RI), juntamente com abordagens teóricas sobre estudos de poder, oferece uma oportunidade bem-vinda para avaliar o processo que motiva o BRICS como um driver para se mudar de tomador de regra para formulador de regra. Portanto, estimula a análise de setores como desenvolvimento, finanças e organizações internacionais, levando-nos a refletir em que medida os novos debates corroboram um cenário em mudança? Ao fazer isso, a pesquisa pretende avaliar a construção de uma ordem internacional na qual um número maior de Estados participa efetivamente da formação de normas e valores no sistema internacional. Palavras-Chave: BRICS. Desenvolvimento. Valores. Sistema Interestatal